Determinants of Youth Unemployment in Urban Duhok: A Logistic Regression Analysis of Duhok's Labor Market - Mohammed, Dilgash Ahmed (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
Youth unemployment remains a critical socioeconomic issue in Duhok City. This study used an online cross-sectional survey (Google Forms) of 2,076 urban residents aged 18–30, conducted from January to March 2025, to assess employment status and sociodemographic predictors of joblessness. The respondents were 37.7 percent female (n = 782) and 62.3 percent male (n = 1,294). Educational attainment included 33.9 percent secondary‐school graduates, 28.2 percent postgraduate degree holders, 21.9 percent undergraduates, 14.2 percent diploma holders, 1.4 percent with no formal education, and 0.3 percent with vocational training. Employment breakdown showed 30.5 percent in full‐time work, 12.9 percent in part‐time roles, 14.0 percent self‐employed, and 38.2 percent unemployed; 3.3 percent were unable to work and 1.1 percent were retired. Enhanced logistic regression analysis (Stata 17) with comprehensive model diagnostics revealed that female sex (OR = 1.43), younger age (OR = 0.97 per year), and lower educational attainment significantly increased the odds of unemployment, with diploma (OR = 0.75), undergraduate (OR = 0.68), and postgraduate (OR = 0.52) credentials offering graduated protection. Gender-stratified analysis and interaction effects (gender × education) provided deeper insights into differential employment barriers. Model fit statistics showed Pseudo R² = 0.142, with good model performance (Hosmer-Lemeshow p = .189). These findings highlight the need for gender-sensitive policies, age-appropriate training, and expanded vocational and higher-education pathways to reduce youth joblessness in the Kurdistan Region. However, the online sampling methodology limits generalizability to digitally connected youth populations only.